Proton-conducting amino acid-modified chitosan nanofibers for nanocomposite proton exchange membranes. (October 2019) - Wang, Shubo; Shi, Lei; Zhang, Shuo; Wang, Hang; Cheng, Bowen; Zhuang, Xupin; Li, Zhenhuan
Graphical abstract: Highlights: Amino acid molecules were immobilized onto chitosan nanofibers to form proton transfer sites. Amino acid-functionalized CS nanofibers were introduced as proton channels for nanocomposite PEMs. Ser-CSNFs/SPSF showed the highest proton conductivity of 0.192 S/cm (80 °C). The embedded AA-CSNFs lowered swelling rate and methanol crossover. Abstract: Proton transfer using amino acids as proton delivery sites is a ubiquitous and important process in organisms. In this study, novel proton-conducting nanofibers were prepared on the basis of a bionic design concept from two perspectives, namely, proton transfer site and proton transfer route, by immobilizing four kinds of amino acids, namely, serine, arginine, lysine, and glycine, onto chitosan (CS) nanofibers. Nanocomposite membranes were then fabricated by filling the pores of the amino acid-functionalized CS nanofiber mats (AA-CSNFs) with sulfonated polysulfone (SPSF). The methanol crossover of the nanocomposite membranes with AA-CSNFs was reduced and their proton conductivity was increased compared with those of pure SPSF membrane. The nanocomposite membrane embedded with the serine-functionalized CS nanofibers exhibited an excellent proton-conducting ability with the highest proton conductivity of 0.192 S/cm at 80 °C. Results indicated that these nanocomposite membranes showed potential for applications in proton exchange membrane fuel cells with superior combined properties.